The History and Current Development of Indigenous People Movements in Indonesia - Ahmad Ridha Mubarak; Rabiatul Adawiyah (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2021)
This paper is based on an argument that discrimination against indigenous religion is a fact of the dynamics of policy interpretations. Therefore, the presence of indigenous people movements such as AMAN (Aliansi Masyarakat Adat Nusantara), offers solutions for indigenous rights' violations, and it also serves as a place for discussion on existing and possible threats upon indigenous communities. The indigenous people movements aim to establish religious freedom as a means to promote indigenous religion rights, particularly the importance of customary land. On the one hand, the state recognizes the rights of indigenous people, but, on the other hand they are prosecuted with hard conditions in realizing their rights